1981
DOI: 10.1111/j.1476-5381.1981.tb09143.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Constants of Isoprenaline and Orciprenaline and Their Relative Efficacies on Guinea‐pig Isolated Atria Determined by Use of an Irreversible Β‐adrenoceptor Antagonist

Abstract: I Dissociation constants (KA) of isoprenaline and orciprenaline were determined for the positive inotropic and chronotropic responses of guinea-pig isolated atria. Cumulative dose-response curves to the agonists were constructed before and after incubation with and washout of the irreversible ,3-adrenoceptor antagonist, Ro 03-7894 1-(5-chloracetylaminobenzfuran-2-yl)-2-isopropylaminoethanol). 2 After 20 min washout, the curves were displaced to the right with depression of the maxima. After 3 h washout, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
2
5
0
Order By: Relevance
“…This confirms previous reports of an increase in cardiac sensitivity to $-adrenoceptor agonists after chronic catecholamine depletion (see Broadley et a1 1984). There was an increase in basal developed tension after reserpine pretreatment which agrees with previous studies (Broadley & Lumley 1977;Tenner et a1 1982;Torphy et a1 1982) and has been interpreted to indicate a change in the excitationcontraction coupling (Tenner et a1 1982). However, the consensus is that the supersensitivity to padrenoceptor agonists is additional to any change in coupling and in the present study it was associated with an increase in P-adrenoceptor binding sites.…”
Section: Discussionsupporting
confidence: 85%
“…This confirms previous reports of an increase in cardiac sensitivity to $-adrenoceptor agonists after chronic catecholamine depletion (see Broadley et a1 1984). There was an increase in basal developed tension after reserpine pretreatment which agrees with previous studies (Broadley & Lumley 1977;Tenner et a1 1982;Torphy et a1 1982) and has been interpreted to indicate a change in the excitationcontraction coupling (Tenner et a1 1982). However, the consensus is that the supersensitivity to padrenoceptor agonists is additional to any change in coupling and in the present study it was associated with an increase in P-adrenoceptor binding sites.…”
Section: Discussionsupporting
confidence: 85%
“…The depression of maximum responses was generally less at the lower temperature, confirming earlier observations (Broadley & Nicholson, 1980) and reflecting the enhanced receptor sensitivity at the lower temperature. Dissociation constants were calculated only after thorough washout of free Ro 03-7894 since any residual antagonist exerts an additional competitive antagonism which distorts the KA value (Broadley & Nicholson, 1981). Furthermore, care was taken to measure equiactive concentrations on the linear portions of pre-and postRo 03-7894 dose-response curves (see Thron, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been shown that the kinetics of agonist and antagonist binding are different (Weiland, Minneman & Molinoff, 1979;1980) and the possibility that the supersensitivity may be the result of an increase in affinity of agonists only, must be considered. With the availability of a 3-adrenoceptor antagonist, Ro 03-7894 (1-(5-chloracetylaminobenzfuran-2-yl)-2-isopropylaminoethanol), which has been shown to behave in an apparently irreversible manner (Nicholson & Broadley, 1978;Nicholson, Broadley, Burden & Natoff, 1979;Rankin & Broadley, 1982), it has been possible to determine pharmacologically the affinities of sympathomimetic amines for cardiac f-adrenoceptors (Broadley & Nicholson, 1981;Siegl & McNeill, 1982). In the present study, the affinities of isoprenaline and orciprenaline were determined as their dissociation constants, in three cardiac preparations of the guineapig, to assess whether changes occur during hypothermia-induced supersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The Macmillan Press Ltd 1984 The concentration of Ro 03-7894 used in the present study (0.6 mM) was similar to that used in the initial in vitro studies with this agent (Nicholson & Broadley, 1978;Broadley & Nicholson, 1981).…”
Section: Introductionmentioning
confidence: 97%
“…In previous studies it has been suggested that the compound Ro 03-7894 (1-(5-chloroacetylaminobenzfuran-2-yl)-2-isopropylaminoethanol) behaves as an irreversible, non-competitive antagonist at Padrenoceptor sites in guinea-pig isolated cardiac tissue (Nicholson & Broadley, 1978;Broadley & Nicholson, 1981;Rankin & Broadley, 1982). The evidence for this classification of the antagonist was based on the observations that it reduced the slope and maxima of positive inotropic and chronotropic concentration-response curves to isoprenaline and orciprenaline without affecting curves established to histamine or calcium (Nicholson & Broadley, 1978).…”
Section: Introductionmentioning
confidence: 99%